Protective effect of treatment with black cumin oil on spatial cognitive functions of rats that suffered global cerebrovascular hypoperfusion - Azzubaidi, Marwan Saad; Saxena, Anil Kumar; A.Talib, Norlelawati; Ahmed, Qamar Uddin; Dogarai, Bashar Bello S. (Polish Neuroscience Society - PTBUN, 2012)
The fixed oil of black cumin seeds, Nigella sativa L. (NSO), has shown considerable antioxidant and anti-inflammatory activities. Chronic cerebral hypoperfusion has been linked to neurodegenerative disorders including Alzheimer’s disease (AD)and its subsequent cognitive impairment in which oxidative stress and neuroinflammation are the principal culprits. Cerebrovascular hypoperfusion was experimentally achieved by bilateral common carotid arteries occlusion (2VO) in rats. Morris water maze (MWM) test was employed to assess the effects of NSO on spatial cognitive function before and after 2VO intervention. Rats were divided into long-term memory (LTM) and short-term memory (STM) groups, each was further subdivided into 3 subgroups: sham control, untreated 2VO and NSO treated 2VO group. All subgroups were tested with MWM at the tenth postoperative week. Working memory test results for both sham control and NSO treated groups showed significantly lower escape latency time and total distance travelled than untreated 2VO group. Similarly, LTM and STM MWM tests for sham control and NSO treated groups revealed significantly better maze test performance as compared to untreated 2VO group. Sham control and NSO treated 2VO groups demonstrated superior probe memory test performance as compared to untreated 2VO group. The fixed oil of Nigella sativa seeds has demonstrated noticeable spatial cognitive preservation in rats challenged with chronic cerebral hypoperfusion which indicates a promising prospective neuroprotective effect.